Shape‐Programmable Architectured Hydrogels Sensitive to Ultrasound. Issue 7 (10th February 2020) - Zhang, Pengfei; Behl, Marc; Balk, Maria; Peng, Xingzhou; Lendlein, Andreas
Abstract: On‐demand motion of highly swollen polymer systems can be triggered by changes in pH, ion concentrations, or by heat. Here, shape‐programmable, architectured hydrogels are introduced, which respond to ultrasonic‐cavitation‐based mechanical forces (CMF) by directed macroscopic movements. The concept is the implementation and sequential coupling of multiple functions (swellability in water, sensitivity to ultrasound, shape programmability, and shape‐memory) in a semi‐interpenetrating polymer network (s‐IPN). The semi‐IPN‐based hydrogels are designed to function through rhodium coordination (Rh‐s‐IPNH). These coordination bonds act as temporary crosslinks. The porous hydrogels with coordination bonds (degree of swelling from 300 ± 10 to 680 ± 60) exhibit tensile strength σmax up to 250 ± 60 kPa. Shape fixity ratios up to 90% and shape recovery ratios up to 94% are reached. Potential applications are switches or mechanosensors. Abstract : Interpenetrating polymer‐network‐based hydrogels, in which both polymeric components can be coupled with dynamic bonds, are shown to be shape programmable. Their shape‐memory can be recalled by exposure to low frequency ultrasound.